Reinforced gel-state polybenzimidazole hydrogen separators for alkaline water electrolysis - Trisno, Muhammad Luthfi Akbar; Dayan, Asridin; Lee, Su Ji; Egert, Franz; Gerle, Martina; Kraglund, Mikkel Rykaer; Jensen, Jens Oluf; Aili, David; Roznowska, Aleksandra; Michalak, Artur; Park, Hyun S.; Razmjooei, Fatemeh; et al. (Royal Society of Chemistry, 2022)
A new membrane fabrication process is presented, in which PBI is cast from a phosphoric acid-based solution and transformed into a KOH doped membrane by immersion in KOH solution. At room temperature, such membranes show a remarkably high conductivity of 300 mS cm(-1) in 25 wt% KOH solution, 3 times higher than that of conventional PBI membranes cast from DMAc. While swelling of PBI in KOH solution is highly anisotropic, the phosphoric acid-cast membrane shrinks isotropically when immersed in KOH solution, indicating that the ordered, presumably lamellar structures, which are suspected to hinder transfer of ions through the membrane, are transferred into a gel-state. This is further supported by WAXS analysis. DFT calculations suggest that the broad signal in WAXS is related to the distance between hydrogen bonded imidazolides. The soft nature of the KOH doped PBI was mitigated by reinforcement with porous supports. By using a PTFE support, the tensile strength increased from 2 to 32 MPa, and the Young's modulus from 19 to 80 MPa. Immersion in 25 wt% KOH at 80 degrees C indicated high stability. In the electrolyzer, a conventional PBI membrane failed within 200 hours. In contrast to this, a PTFE-supported separator reached 1.8 A cm(-2) at 1.8 V and was operated for 1000 hours without failure, which is the longest operation time for ion-solvating membranes to date.